(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Tuberculosis (TB) remains one of the world’s leading infectious causes of morbidity and mortality, despite decades of public health efforts and the availability of effective treatment. This narrative review explores the current understanding of the epidemiology, clinical features, diagnostic approaches, and challenges related to treatment failure in TB. Globally, an estimated 10 million new TB cases and 1.3 million TB-related deaths were reported in 2022, with the burden disproportionately affecting low- and middle-income countries. Risk factors such as HIV co-infection, malnutrition, poverty, and crowded living conditions contribute significantly to disease transmission and persistence. Clinically, TB primarily affects the lungs but can involve almost any organ, presenting with a wide spectrum of symptoms ranging from persistent cough, fever, night sweats, and weight loss to non-specific signs in extra-pulmonary cases. Early and accurate diagnosis is crucial for controlling the spread and improving patient outcomes. Conventional diagnostic methods such as sputum smear microscopy have limited sensitivity, while newer tools like GeneXpert MTB/RIF and culture methods have improved diagnostic accuracy but face challenges of cost and accessibility in resource-limited settings. Despite standardized treatment regimens, treatment failure remains a critical issue due to factors including non-adherence, drug resistance, inadequate healthcare infrastructure, and patient-related social determinants. Multidrug-resistant TB (MDR-TB) and extensively drug-resistant TB (XDR-TB) have emerged as major threats to global TB control, requiring longer, more toxic, and costlier treatment courses with variable success rates. Addressing treatment failure demands a multifaceted approach, incorporating patient education, community-based support, strengthened healthcare systems, and robust public health policies. This review underscores the need for continuous innovation in diagnostics, treatment regimens, and patient-centered interventions to achieve global targets for TB elimination. Journal of National Institute of Neurosciences Bangladesh, July 2024;10(2):130-137